Pendekatan Modern terhadap l'jaz Al-Qur'an - M. Rafi Yunus (Al-Jami'ah: Journal of Islamic Studies, 2002)
I’jaz  al-Qur'an is one of the important dogma in Islam; it is derived from many Qur'anic verses. The dogma stipulates that the Qur'an is inimitable. But what is inimitable in the Qur'an remains to be discussed among Muslim scholars. At the outset of development of the study of the Qur'an, the classical writers considered the balaghah (rhetorical excellence) of the Qur'an to be its I’jaz. They argue that though the Qur'an did not specify this, one can understand that the Arabs -with all their expertise in the field of literary genre- was challenged to produce a piece of work, as eloquence as the Qur'an. On the other hand, modern writers considered that what is inimitable in the Qur'an was not only its balaghah but also its contents in general, and its messages. The contents and messages of the Qur'an, which are carefully knitted in an excellent balaghah constitute the most Solid materials that are inimitable by anyone. The paper presents, describes, and to some points, compares, the theories of classical and modem writers among Muslim scholars concerning I’jaz aI-Qur'an, to find out the features of modern theories that was not yet elaborated in the classical theories.